Trauma-Informed Care Training in U.S. and Canadian Ob/Gyn Residencies - DeAndrade, Samantha (Violence against women, 2025)
This is a cross-sectional study investigating the prevalence and nature of trauma-informed care (TIC) training in obstetrics and gynecology residency programs. In our sample, 20% of programs had annual TIC training, 53% had less than annual training, and 27% had no training at all. Only 25.3% of respondents were satisfied with their current training in interpersonal trauma and TIC. A lack of facilitators to conduct such training was the primary barrier to implementing TIC. Significant opportunity exists to improve TIC education for Ob/Gyn trainees.